Sloterdijk y Canetti: el detonante iconográfico y operístico de la política de masas - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The mass, like a ontologic prolongation of the individual, shows some of the properties of this one: one becomes distressed, it is excited, it protected, becomes rich, it is developed and it concluded. Thus, between the main attributes that can be recognized in the mass they are the compultion to grow in number and concentration; the mass loves the density and it always moves towards something; the masses drag bodies, infect and cause collective kinetic excitations, obtain that, suddenly, everything is filled. In the scorn of the masses; Test on the cultural fights in the modern society, states the dissolution of the dream of the autotransparente group and the persistence of an pseudo-emancipation state from which the mass unloads its energy and eliminates bourgeois distances, it is congregated before himself and for himself, although no longer it are expressed in a physical assembly but through massive means of communication.